Study on the integration effect of multiple vehicles' delayed velocities on traffic stability in intelligent transportation system environment. Issue 2 (3rd August 2020) - Zhang, Geng; Ma, Qinglu; Pan, Dongbo; Zhang, Yu; Huang, Qiaoli; Jiang, Shan
Abstract : Purpose: In an intelligent transportation system (for short, ITS) environment, a vehicle's motion is affected by the information in a large scale. The purpose of this paper is to study the integration effect of multiple vehicles' delayed velocities on traffic flow. Design/methodology/approach: This paper constructed a new car-following model to study the integration effect of multiple vehicles' delayed velocities on traffic flow. The new model is analyzed by linear and nonlinear perturbation method theoretically and also verified by simulation. Findings: It is found out that the integration of preceding vehicles' delayed velocities affect the stability of traffic flow importantly, and three preceding vehicles' delayed velocities information should be considered in real traffic. Originality/value: The new car-following model by considering the integration effect of multiple vehicles' delayed velocities is firstly proposed in this paper. The research result shows that three preceding vehicles' delayed velocities information is the best choice to stabilizing traffic flow.